Serum extracellular vesicles containing MIAT induces atrial fibrosis, inflammation and oxidative stress to promote atrial remodeling and atrial fibrillation via blockade of miR‐485‐5p‐mediated CXCL10 inhibition. Issue 8 (3rd August 2021) - Chen, Yingwei; Chen, Xiaojie; Li, Haiyu; Li, Yunpeng; Cheng, Dong; Tang, Yi; Sang, Haiqiang
Abstract: Background: Atrial fibrillation (AF), a supraventricular arrhythmia that impairs cardiac function, is a main source of morbidity and mortality. Serum‐derived extracellular vesicles (EVs) have been identified to carry potential biomarker or target for the diagnosis and treatment of AF. We intended to dissect out the role of lncRNA MIAT enriched in serum‐derived EVs in AF. Methods: MIAT expression was quantified in EVs isolated from serum samples of AF patients. Mouse and cell models of AF were developed after angiotensin II (Ang II) induction. Relationship between MIAT, miR‐485‐5p, and CXCL10 was identified. Ectopic expression and depletion assays were implemented in Ang II‐treated mice or HL‐1 cells, or those co‐cultured with serum‐derived EVs to explore the roles of EV‐carried MIAT. Results: MIAT was upregulated in EVs from serum samples of AF patients. Further analysis indicated that MIAT enriched in serum‐derived EVs promoted atrial fibrosis, inflammation and oxidative stress, and aggravated the atrial remodeling and resultant AF. Mechanistically, MIAT bound to miR‐485‐5p and weakened its inhibitory role on the target CXCL10, which was responsible for the role of serum‐derived EV containing MIAT in cellular fibrosis, oxidative stress and inflammation, and atrial remodeling in vivo. Conclusions: In conclusion, serum‐derived EV containing MIAT facilitates atrial remodeling and exacerbates the AF by abolishing the miR‐485‐5p‐mediated CXCL10 inhibition. This finding aids in the deeper understanding about the pathophysiology of AF. Abstract : EVs isolated from serum samples of AF patients carried MIAT to bind to miR‐485‐5p and caused the upregulation of the miR‐485‐5p target CXCL10, inducing atrial myocyte fibrosis, inflammation, and oxidative stress, thus promoting atrial remodeling and aggravating the AF.